1981
DOI: 10.2165/00003088-198106050-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics of Nitrazepam

Abstract: Nitrazepam is one of the oldest benzodiazepines and is widely used as an hypnotic throughout the world, except North America, where it is not available. It is a safe hypnotic, with low acute toxicity and minor side effects. Development of tolerance or dependence and withdrawal symptoms are rare and very few known interactions with other drugs exist.The absorption of nitrazepam from the gastrointestinal tract is fairly rapid (t mJJx ranging 0.5 to 7 hours). The bioavailability after oral intake averages about 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 72 publications
1
13
1
Order By: Relevance
“…Assuming that unchanged nitrazepam represents 50% of the total radioactivity, the -milk concentrations observed previously (Rieder & Wendt, 1973), would be 2-3 times higher than ours under similar study conditions. Others (Kangas & Breimer, 1981) have reported plasma concentrations of nitrazepam similar to ours.…”
Section: Milk Transfersupporting
confidence: 90%
See 1 more Smart Citation
“…Assuming that unchanged nitrazepam represents 50% of the total radioactivity, the -milk concentrations observed previously (Rieder & Wendt, 1973), would be 2-3 times higher than ours under similar study conditions. Others (Kangas & Breimer, 1981) have reported plasma concentrations of nitrazepam similar to ours.…”
Section: Milk Transfersupporting
confidence: 90%
“…Nitrazepam, which has a mean elimination half-life of 29 h, accumulates in plasma and causes impaired psychomotor function on the day after administration (Kangas & Breimer, 1981). Thus, a shorter acting hypnotic may be preferable for use in the maternity ward.…”
Section: Introductionmentioning
confidence: 99%
“…Its disposition in normal young subjects has been fairly well studied (Jochemsen et al, 1982a,b;Kangas etal., 1979a;Kangas & Breimer, 1981), but there is little information about elderly people and none at all about patients with liver disease. Castleden et al (1977), who measured nitrazepam plasma concentrations at 12, 36 and 60 h after administration and determined elimination halflives, suggested that nitrazepam kinetics is not influenced by age, whereas Kangas etal.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the piperazine N-oxide of loprazolam may have pharmacological activity approaching that of the parent drug (Miller, unpublished Our findings provide evidence that the absorption of loprazolam can be slow. Mean time to peak serum concentration was considerably greater than that usually quoted for benzodiazepines used as hypnotics (Breimer, 1979; 0E Curry & Whelpton, 1979;Greenblatt et al, 1981;Kangas & Breimer, 1981) and there was a marked lag time, on average 1-1.5 h after drug administration, before loprazolam was detectable in serum. Although onset of activity depends on concentration-effect relationships which are unknown for loprazolam, rate of absorption is usually the rate limiting factor in the transfer of drug molecules to their sites of action in the central nervous system, after oral dosing (Curry & Whelpton, 1979).…”
Section: Methodsmentioning
confidence: 71%
“…Furthermore, secondary peaks of unchanged loprazolam and RIA measured material occurred frequently. Similar observations have been made with loprazolam (Stevens et al, 1983) and other benzodiazepines (Breimer etal., 1977;Kangas & Breimer, 1981;Korttila & Kangas, 1977) and may relate to ingestion of food. Where secondary peaks represent the maximum serum concentrations of the drug, they may have an important influence on the assessment of absorption, but whether they denote pharmacologically active drug remains to be established.…”
Section: Methodsmentioning
confidence: 99%